2021
DOI: 10.1590/1678-4685-gmb-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

A new view on the scenario of karyotypic stasis in Epinephelidae fish: Cytogenetic, historical, and biogeographic approaches

Abstract: Epinephelidae (groupers) is an astonishingly diverse group of carnivorous fish widely distributed in reef environments around the world, with growing economic importance. The first chromosomal inferences suggested a conservative scenario for the family. However, to date, this has not been validated using biogeographic and phylogenetic approaches. Thus, to estimate karyotype diversification among groupers, eight species from the Atlantic and Indian oceans were investigated using conventional cytogenetic protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…These chromosomes were 1, 2 and 4 where, based on BAC clone synteny studies, other pericentric rearrangements (inversions), that have occurred during the evolution of these chromosomes were described (Rodrıǵuez et al, 2019, Rodrıǵuez et al, 2021Ramıŕez et al, 2022). There is evidence to support that inversions, as well as other chromosomal rearrangements, are involved in the adaptation of species to the environment and that polymorphisms associated with these inversions are related to geographic distributions (Wellenreuther and Bernatchez, 2018;Amorim et al, 2021). TEs are considered key elements in this chromosomal rearrangement process (Feschotte and Pritham, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These chromosomes were 1, 2 and 4 where, based on BAC clone synteny studies, other pericentric rearrangements (inversions), that have occurred during the evolution of these chromosomes were described (Rodrıǵuez et al, 2019, Rodrıǵuez et al, 2021Ramıŕez et al, 2022). There is evidence to support that inversions, as well as other chromosomal rearrangements, are involved in the adaptation of species to the environment and that polymorphisms associated with these inversions are related to geographic distributions (Wellenreuther and Bernatchez, 2018;Amorim et al, 2021). TEs are considered key elements in this chromosomal rearrangement process (Feschotte and Pritham, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Inversions are important rearrangements that lead to polymorphism maintenance events in populations through balancing selection and are also important in the speciation process [49,50]. In addition, there is much evidence to support the view that inversions are involved in the environmental adaptation of species and that inversion polymorphisms within a species are related geographically [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Integrative cytogenetic approaches in marine fish groups have indicated that specific biological aspects and historical contingency can act together as causal effects of chromosomal changes [ [1] , [2] , [3] ]. Marine fishes display contrasting karyotype evolution patterns, which can vary from high dynamic rates to stasis, a process in which chromosomal change rates are absent or slow, allowing chromosomal patterns to persist for long periods of time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 , 43 ]). Repeated sequences, such as rDNA, have been linked to mechanisms that promote chromosomal rearrangements [ 16 , 44 , 45 ], interpopulation variations [ 1 , 46 ], karyotypic diversification [ 12 , 47 , 48 ], or serve as markers to track karyotypic trends in broader biogeographical contexts [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%